3D particle-in-cell modeling of Langmuir probe effective collecting area in magnetized plasma. (14th June 2018) - Podolník, A; Komm, M; Adámek, J; Háček, P; Krbec, J; Dejarnac, R; Gunn, J P; Pánek, R
Abstract: Langmuir probes are a widespread tool for measurement of important plasma parameters such as electron temperature T e, plasma electron density n e, ion saturation current I sat and the floating potential V fl, which are obtained from a fit to the current–voltage ( I – V ) characteristic of the probe. In magnetized plasmas, the measurements can be affected by sheath expansion due to large negative bias voltages, which is addressed by the introduction of a fourth parameter to the fitting function correcting the values of all measured quantities. In order to derive the plasma density from I sat, the understanding of probe ion collection is needed. In magnetized plasmas, the collecting area may not correspond to the real geometrical probe surface due to ion finite Larmor effects and so the derivation of I sat (and hence n ) can be rather complicated. In this work, the influence of magnetic fields on the probe effective collecting area is studied by the means of fully 3D3V particle-in-cell model SPICE3. A parameter scan based on properties of scrape-off layer plasmas at COMPASS tokamak as well as a particular probe pin used on a horizontal reciprocating manipulator is performed. The results reveal that the presence of the probe head has a substantial effect on the outcome of the measurement as it forms a magnetic presheath at the probe location. An approximate formula for addressing the change of effective collecting area is presented and the data from the simulations are compared to measurements of COMPASS reciprocating probes and lithium beam emission spectroscopy.